The secret - Byrne, Rhonda (Simon & Schuster, 2006)
Once known only by an elite who were unwilling to share their knowledge of the power, 'the secret' of obtaining anything you desire is now revealed by prominent physicists, authors and philosophers as being based in the universal Law of Attraction. And the good news is that anyone can access its power to bring themselves health, wealth and happiness. Fragments of The Secret have been found in oral traditions, literature, religions and philosophies throughout the centuries.